Immunomics-Guided Antigen Discovery for Praziquantel-Induced Vaccination in Urogenital Human Schistosomiasis - Pearson, Mark S.; Tedla, Bemnet A.; Becker, Luke; Nakajima, Rie; Jasinskas, Al; Mduluza, Takafira; Mutapi, Francisca; Oeuvray, Claude; Greco, Beatrice; Sotillo, Javier; Felgner, Philip L.; Loukas, Alex (Frontiers in Immunology, 2021)
Despite the enormous morbidity attributed to schistosomiasis, there is still no vaccine to combat the disease for the hundreds of millions of infected people. The anthelmintic drug, praziquantel, is the mainstay treatment option, although its molecular mechanism of action remains poorly defined. Praziquantel treatment damages the outermost surface of the parasite, the tegument, liberating surface antigens from dying worms that invoke a robust immune response which in some subjects results in immunologic resistance to reinfection. Herein we term this phenomenon Drug-Induced Vaccination (DIV). To identify the antigenic targets of DIV antibodies in urogenital schistosomiasis, we constructed a recombinant proteome array consisting of approximately 1,000 proteins informed by various secretome datasets including validated proteomes and bioinformatic predictions. Arrays were screened with sera from human subjects treated with praziquantel and shown 18 months later to be either reinfected (chronically infected subjects, CI) or resistant to reinfection (DIV). IgG responses to numerous antigens were significantly elevated in DIV compared to CI subjects, and indeed IgG responses to some antigens were completely undetectable in CI subjects but robustly recognized by DIV subjects. One antigen in particular, a cystatin cysteine protease inhibitor stood out as a unique target of DIV IgG, so recombinant cystatin was produced and its vaccine efficacy assessed in a heterologous Schistosoma mansoni mouse challenge model. While there was no significant impact of vaccination with adjuvanted cystatin on adult worm numbers, highly significant reductions in liver egg burdens (45-55%, P<0.0001) and intestinal egg burdens (50-54%, P<0.0003) were achieved in mice vaccinated with cystatin in two independent trials. This study has revealed numerous antigens that are targets of DIV antibodies in urogenital schistosomiasis and offer promise as subunit vaccine targets for a drug-linked vaccination approach to controlling schistosomiasis.